Editorial: evolving histological assessment of NASH. Issue 11 (10th November 2019) - Rowe, Ian A.
Abstract : LINKED CONTENT This article is linked to Pai et al papers. To view these articles, visit https://doi.org/10.1111/apt.15503 and https://doi.org/10.1111/apt.15570 .